Association of neuroinflammation with episodic memory: a [11C]PBR28 PET study in cognitively discordant twin pairs. Issue 1 (14th April 2020) - Lindgren, Noora; Tuisku, Jouni; Vuoksimaa, Eero; Helin, Semi; Karrasch, Mira; Marjamäki, Päivi; Kaprio, Jaakko; Rinne, Juha O
Abstract: Alzheimer's disease is associated with chronic response of innate immune system, referred as neuroinflammation. PET radioligands binding to the 18 kDa translocator protein are potential biomarkers of neuroinflammation. Translocator protein PET studies in mild cognitive impairment and Alzheimer's disease have indicated controversial results, possibly reflecting interindividual variation and heterogeneity of study populations. We controlled for genetic and environmental effects by studying twin pairs discordant for episodic memory performance. Episodic memory impairment is a well-known cognitive hallmark of early Alzheimer's disease process. Eleven same-sex twin pairs (four monozygotic pairs, six female pairs, age 72–77 years) underwent [ 11 C] N -acetyl- N -(2-methoxybenzyl)-2-phenoxy-5-pyridinamine ([ 11 C]PBR28) PET imaging, structural magnetic resonance imaging and neuropsychological testing in 2014–17. Main PET outcome was the volume-weighted average standardized uptake value of cortical regions vulnerable to Alzheimer's disease pathology. Ten pairs were discordant for episodic memory performance. In the eight pairs with identical translocator protein genotype, twins with poorer episodic memory had ∼20% higher cortical [ 11 C]PBR28 binding compared with their better-performing co-twins (mean intra-pair difference 0.21 standardized uptake value, 95% confidence interval 0.05–0.37, P  = 0.017). The result remained the same when including all discordant pairs and controlling for translocator protein genotype. Increased translocator protein PET signal suggests that increased microglial activation is associated with poorer episodic memory performance. Twins with worse episodic memory performance compared with their co-twins had on average 20% higher uptake of the neuroinflammatory marker translocator protein PET tracer 11 [ 11 C]PBR28. The findings support a negative association between neuroinflammation and episodic memory and the use of translocator protein positron emission tomography as a useful indicator of Alzheimer's disease process. Abstract : Twins with worse episodic memory performance compared with their co-twins had on average 20% higher uptake of the neuroinflammatory marker translocator protein PET tracer 11 [ 11 C]PBR28. The findings support a negative association between neuroinflammation and episodic memory and the use of translocator protein positron emission tomography as a useful indicator of Alzheimer's disease process. Graphical Abstract: